Comparative analysis of IL-1β blood serum concentration, neutrophil-to-lymphocytes ratio in peripheral blood, and the levels of PD-L1 expression in malignant tissues of the patients with various solid tumors - R. V. Orlova; N. V. Zhukova; A. M. Malkova; E. A. Kaledina; A. R. Gubal; V. V. Sharoiko (Медицинская иммунология, 2021)
The action of checkpoint inhibitors is based on activation of T cell antitumor immunity, and, therefore, the search for markers of lymphocyte functional activity before starting the therapy is highly relevant. Determination of the PD-L1 expression in tumor tissues reflects immunosuppressive activity of malignant cells, and it is used as a predictive marker in clinical practice. The ratio of neutrophils to lymphocytes in tumor tissue and in peripheral blood can also indicate the activity of adaptive immunity and correlates with the efficacy of therapy. It has been shown that a high level of interleukin 1 beta in the tumor microenvironment is associated with immunosuppression of lymphocytes and, possibly, reflects the activity of the tumor microenvironment. The aim of this work is to study the relationship between tumor expression of PD-L1, the concentration of serum interleukin-1 beta and the ratio of neutrophils and lymphocytes in peripheral blood.Before starting therapy with checkpoint inhibitors in patients with various solid tumors (n = 50), the serum level of interleukin-1 beta was determined by ELISA (ELISA-Best, Novosibirsk, Russia), expression of PD-L1 in the tumor by immunohistochemical method, complete blood count was performed using cytometry. Statistical analysis was performed in GraphPad Prism 6 (Graph Pad Software, USA) using the statistical methods of Fisher, Mann-Whitney, and Spearman.The average value of the index of the ratio of neutrophils and lymphocytes (NLR) in peripheral blood was 2.65± 0.21 (95% CI 2.22-3.07). The index value of more than 3.5 was found in 18% (9/50) of patients. The mean value of the PD-L1 expression level was 23.02±4.52% (95% CI 13.86-32.18). Expression of PD-L1 in tumor tissue was detected in 60.1% (25/40) of patients, among whom an increased expression of more than 50% was detected in 20.0% (5/25) of cases. A positive weak correlation was found between the concentration of interleukin 1 beta and the number of leukocytes (r = 0.34; p = 0.019) and index (r = 0.32; p = 0.029). The level of PD-L1 expression in tumor tissue also had a weak positive correlation with the serum interleukin 1 beta concentration (r = 0.33; p = 0.037) and the neutrophil-lymphocyte ratio (r = 0.33; p = 0.034). In the group of patients with PD-L1 expression > 5%, the mean value of the concentration of interleukin 1 beta was 1.65±0.62 pg/ml, and the mean value of the index was 4.26±0.94 х 10 9/l, which exceeds the values groups with undetectable PD-L1, but the differences were not statistically significant.The obtained result may indicate the influence of the immunosuppressive properties of the tumor on the state of the patient's immunity. Comprehensive determination of tumor PD-L1 expression, serum interleukin 1 beta concentration and the ratio of neutrophils and lymphocytes in peripheral blood can be used as an assessment of the patient's immune status before starting treatment with checkpoint inhibitors.